PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE LEARNING TOURNAMENT TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 17 PADANG - Alfadhli, Alfadhli; Zulfaneti, Zulfaneti; Lovia, Lita (STKIP PGRI Sumbar, 2014)
ABSTRACTÂ This research was background by the understanding of studentsâ mathematic concept which was still low and the responsibility of students who lack the given task during the learning process takes place. This case saw from the result of learning math by students grade eight at SMP N 17 Padang academic year 2013-2014. The purpose of this research was what is the understanding of studentsâ mathematic concept which applied the active learning strategy type learning tournament better than applied conventional learning for students grade eight at SMP N 17 Padang. This research was experimental research and the research design was random sampling. The population was all of students grade eight at SMP N 17 Padang academic year 2013-2014 which was divided into eight classes. The technique to collect the sample was random, and chooses class VIII 4 as an experimental class and VIII 5 as a control class. The research instrument was understanding test of mathematic concept. The test that used was essay with reability 0,777. The data analysis technique was the one-sided t test with Minitab. Based on data analysis, have known that the sample class did have normal contribution. The result of hypothesis test found p-value = 0,045 little than normal standard = 0,05. So, the hypothesis was accepted. The conclusion was the understanding of studentsâ mathematic concept which applied the active learning strategy type learning tournament better than applied conventional learning. Â